PengaruhUtangdan PerputaranModalKerjaTerhadapProfitabilitasPerusahaan(Studi Kasus Pada PT Bumi Sekar Tbk Periode 2013-2018) - Saprudin, Saprudin; Hartono, Bayu (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
This study aims to determine how much influence the debt, working capital turnover has on the profitability of PT Sekar Bumi Tbk. Debt is proxied by DER, working capital turnover is proxied by WCT, while profitability is proxied by ROA. Based on the nature of the data used in this study is a type of quantitative research. Samples were taken, namely PT Sekar Bumi Tbk with the objectof research of 2013-2018 financial statements. Linear regression analysis was used in this study, with the help of SPSS software for Windows 20.0. The results of this study explain that partially DER has a significant effect on ROA, and has a very strong relationship of 83.9%. WCT has no significant effect on ROA, and has a very weak relationship of 18.4%. However, simultaneously DER and WCT has a significant effect with a contribution of 70.8% to ROA. So companies need to pay attention and consider how much effective the use of debt as a source of funding for the company.